Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1029/93jc00996
|View full text |Cite
|
Sign up to set email alerts
|

Shorerise and bar‐berm profiles on ocean beaches

Abstract: A beach equilibrium model is developed that treats the outer (shorerise) portion of the profile independently from that of the inner (bar‐berm) portion. The two portions are matched at the breakpoint‐bar. The partitioning of the profile in this way is consistent with the different forcing modes on either side of the breakpoint. This formulation utilizes beach profile data not previously available. It is shown that both portions of the profile are well fitted by curves of the form h = Axm, where h is positive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 25 publications
5
69
0
7
Order By: Relevance
“…(1) also leads to the estimate of the so-called "fitting depth", i.e., the water depth at which the measured profile collapse over the equilibrium profile. Though recent models account for further parameters, like seasonal changes (Inman et al, 1993) or the generation of submerged bars (Holman et al, 2014), their application is fairly difficult and it has been demonstrated that Eq. (1) properly represents the long-term natural profile, to be used for coastal engineering purposes (e.g., Walton and Dean, 2007;Soldini et al, 2013).…”
Section: Description Of the Sitementioning
confidence: 99%
“…(1) also leads to the estimate of the so-called "fitting depth", i.e., the water depth at which the measured profile collapse over the equilibrium profile. Though recent models account for further parameters, like seasonal changes (Inman et al, 1993) or the generation of submerged bars (Holman et al, 2014), their application is fairly difficult and it has been demonstrated that Eq. (1) properly represents the long-term natural profile, to be used for coastal engineering purposes (e.g., Walton and Dean, 2007;Soldini et al, 2013).…”
Section: Description Of the Sitementioning
confidence: 99%
“…However, it is well known that a one-year-long beach evolution occurs through a series of "stages" (expressed by different topographic profiles) which endpoints are represented by the winter and summer profiles (see again Figure 2) [83]- [87]. These stages result from cut and fill alternations over seasons, producing beach profiles that show changes in form, being higher and wider after phases of accretion and lower and flatter (with a backing rise or cliff) after phases of erosion [7].…”
Section: Temporal Scale Of the Observationsmentioning
confidence: 99%
“…One campaign was at the end of the summer of 2003 and another at the end of the winter of 2003-2004 in order to characterise the principal morphodynamic equilibrium states of the beaches (Wright et al [7] and Short [5] Best fit was found in most of the cases by using two Dean Profiles. One for the intertidal part of the profile (A 1 ) and another for the submerged part (A 2 ) (Inman et al [2]). In order to understand the main seasonal sand movements inside the Bay, data from the summer and winter topo-bathymetric campaigns data were compared (see Figure 6).…”
Section: Medium Termmentioning
confidence: 99%